2019
DOI: 10.4315/0362-028x.jfp-18-298
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Antimicrobial Interventions for Reducing Shiga Toxin–Producing Escherichia coli Surrogate Populations during Goat Slaughter and Carcass Chilling

Abstract: Demand and consumption of goat meat is increasing in the United States due to an increase in ethnic populations that prefer goat meat. As ruminant animals, goats are known reservoirs for Shiga toxin–producing Escherichia coli (STEC) and proper handling, especially during slaughter, is imperative to reduce the likelihood of carcass and meat contamination. However, the majority of antimicrobial intervention studies during the slaughter of ruminant species have focused on beef, highlighting the need for validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Foreshank and chuck trim were chosen as the “worst case scenario” for this section as, historically, these are the two types of trim that the commercial beef processing plant had more frequently found presumptive E. coli O157:H7 presence. These surrogates have been previously seen to mimic E. coli O157:H7 and Salmonella resistance to antimicrobial treatments when used as a cocktail in validation trials [ 13 , 14 , 15 , 16 , 22 ]. In some cases, reporting a slight increase in the magnitude of survival of the surrogate compared to Salmonella or E. coli O157:H7 for a relatively higher margin of safety.…”
Section: Discussionmentioning
confidence: 99%
“…Foreshank and chuck trim were chosen as the “worst case scenario” for this section as, historically, these are the two types of trim that the commercial beef processing plant had more frequently found presumptive E. coli O157:H7 presence. These surrogates have been previously seen to mimic E. coli O157:H7 and Salmonella resistance to antimicrobial treatments when used as a cocktail in validation trials [ 13 , 14 , 15 , 16 , 22 ]. In some cases, reporting a slight increase in the magnitude of survival of the surrogate compared to Salmonella or E. coli O157:H7 for a relatively higher margin of safety.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found effective results for reducing APC, improvements in color, and no difference in sensory. Thomas et al (2019) used goats carcasses artificially contaminated, washed with water, and treated with organic acids at prechill and 24 h postchill. The solutions tested positive for reducing STEC E. coli surrogate and minor color changes.…”
Section: Microbiological Effects Of Using Organic Acids Solutions On ...mentioning
confidence: 99%